Socialization of Critical HIV/AIDS Condition Prevention Measures - Riani Riani; Hariyet Rinancy; Milda Hastuty (Journal of Community Service and Empowerment, 2025)
The negative stigma against HIV/AIDS sufferers is still a serious problem in society. Many individuals assume that this disease is the result of deviant moral behavior, so sufferers often experience social discrimination, such as being ostracized and shunned. Some people still believe that HIV/AIDS is just a rumor created for the benefit of the pharmaceutical industry. In Riau Province in 2024, it was recorded that 4,018 individuals had reached the AIDS stage, with an increase in new cases of 86%. However, many sufferers are reluctant to get themselves checked if they have not experienced severe symptoms, which causes delays in treatment, leading to critical conditions and increasing mortality rates. This community service program was carried out in response to the low understanding of partners regarding the sources of transmission, risk factors, and complications of HIV/AIDS. Therefore, the community service team carried out education on preventing critical conditions of HIV/AIDS. After the socialization, partners showed an increased understanding of the differences in HIV/AIDS symptoms according to stage, recognized risk factors, and committed to avoiding risky behavior. In addition, partners took the initiative to support government programs to reduce the number of HIV/AIDS cases in the community.